Integration of Reading and New Literacies with Islamic Education - Maspul, Kurniawan Arif (Jurnal Penelitian Ilmu Ushuluddin, 2024)
This review looks at how reading and new literacies are being integrated into Islamic education. It discusses the issues faced by educators and learners, assesses alternative approaches, and evaluates their compatibility with growing literacies and Islamic beliefs using case studies from "Literacy and Libraries: Learning from Case Studies". The review emphasizes the significance of a balanced literacy approach as well as the incorporation of digital and multimodal literacies. It emphasizes the significance of libraries in enhancing students' reading skills and equipping them for success in the modern world while respecting Islamic values. The findings provide important insights for supporting effective reading and new literacies integration within an Islamic educational framework.